Prospective study using Apache II scoring to predict the outcomes of patients undergoing emergency gastrointestinal procedure - Shelgaonkar, Vaishali C.; Butey, Swatika P.; Nandagawali, Vishal R. (International Surgery Journal, 2021)
Background: Many scoring systems have been used to assess the morbidity and mortality of patients presenting with acute abdomen, of which Apache II (acute physiology and chronic health evaluation) score has been accepted widely. This study predicted the effectiveness of Apache II scoring system as a potential clinical and research tool which could be included as routine part of patient assessment to predict the morbidity and mortality in patients undergoing emergency gastrointestinal procedures. Methods: This study was conducted in the surgical intensive care unit of our tertiary care hospital. It was a prospective observational study done over a period of one year where we assessed the efficacy of Apache II score in eighty two patients. Results: The Apache II scores were divided into three categories, 0-15 low risk group, 16-30 moderate risk group and 31-45 high risk group. There were 25 patients in the low risk group with all being satisfactorily discharged. With 44 patients in the moderate risk group 13 expired (29.54% mortality) and out of 13 patients in the high risk group 11 patients died (84.61% mortality). Conclusions: In the present study the APACHE II scores have correlated well with the outcomes and ICU stay of the patient groups.